2014
DOI: 10.1097/aln.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation versus Rehabilitation

Abstract: Meaningful changes in postoperative functional exercise capacity can be achieved with a prehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
340
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 679 publications
(356 citation statements)
references
References 39 publications
10
340
0
6
Order By: Relevance
“…A prospective trial examining how patients who underwent a prehabilitation regimen prior to colorectal surgery did show that patients who had the largest gains in prehabilitation were more likely to return to their baseline functional scores but did not note any difference in complications [26]. Similarly patients undergoing prehabilitation had no difference in surgical outcomes compared to those undergoing post-operative rehabilitation [27,28]. A single study has shown that prehabilitation improves hospital lengths of stay without effecting complications for colorectal surgery patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective trial examining how patients who underwent a prehabilitation regimen prior to colorectal surgery did show that patients who had the largest gains in prehabilitation were more likely to return to their baseline functional scores but did not note any difference in complications [26]. Similarly patients undergoing prehabilitation had no difference in surgical outcomes compared to those undergoing post-operative rehabilitation [27,28]. A single study has shown that prehabilitation improves hospital lengths of stay without effecting complications for colorectal surgery patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, enhanced benefits relating to urinary incontinence were found for prehabilitative PFMT [19]. Other studies not included in the review (because they did not meet one or more eligibility criteria) found improved outcomes for patients in the prehabilitation versus rehabilitation period, for example, combined interventions for patients with colorectal (exercise, nutrition and counselling) [30] or lung cancer (exercise and nutrition) [31]. Pre-operative exercise for lung cancer patients was associated with a number of benefits for patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in recent years have focused on physical “prehabilitation” to decrease post-operative complications and/or improve post-operative physical function (7275), but to the best of our knowledge no study has evaluated whether physical and/or cognitive prehabilitation might decrease the risk of POCD. The plasticity of the human brain in response to both physical (76) and cognitive (77) exercise suggest that such interventions may help prevent and/or treat POCD.…”
Section: Who Is At Risk For Developing Pocd?mentioning
confidence: 99%